Re-evaluating the costs and limits of adaptive phenotypic plasticity - Auld, Josh R. (The Royal Society, 2010)
When the optimal phenotype differs among environments, adaptive phenotypic plasticity can evolve unless constraints impede such evolution. Costs and limits of plasticity have been proposed as important constraints on the evolution of plasticity, yet confusion exists over their distinction. We attempt to clarify these concepts by reviewing their categorization and measurement, highlighting how costs and limits are defined in different currencies (and may describe the same phenomenon). Conclusions from studies that measure the costs of plasticity have been equivocal, but we caution that these conclusions may be premature owing to a potentially common correlation between environment-specific trait values and the magnitude of trait plasticities (i.e. multi-collinearity) that results in imprecise and/or biased estimates of the costs. Meanwhile, our understanding of the limits of plasticity, and how they may be underlain by the costs of plasticity, is still in its infancy. Based on our re-evaluation of these constraints, we discuss areas for future research.